The relative impact of toxic heavy metals (THMs) (arsenic (As), cadmium (Cd), chromium (Cr)(VI), mercury (Hg), and lead (Pb)) on the total environment: an overview - Rahman, Zeeshanur; Singh, Ved Pal (Environmental monitoring and assessment, 2019)
Certain five heavy metals viz. arsenic (As), cadmium (Cd), chromium (Cr)(VI), mercury (Hg), and lead (Pb) are non-threshold toxins and can exert toxic effects at very low concentrations. These heavy metals are known as most problematic heavy metals and as toxic heavy metals (THMs). Several industrial activities and some natural processes are responsible for their high contamination in the environment. In recent years, high concentrations of heavy metals in different natural systems including atmosphere, pedosphere, hydrosphere, and biosphere have become a global issue. These THMs have severe deteriorating effects on various microorganisms, plants, and animals. Human exposure to the THMs may evoke serious health injuries and impairments in the body, and even certain extremities can cause death. In all these perspectives, this review provides a comprehensive account of the relative impact of the THMs As, Cd, Cr(VI), Hg, and Pb on our total environment.